Biogas production from poultry manure wastewater using soil mixed culture - Nina Farhana, Mohd Jamaludin (2016)
The resource limitation of fossil fuels and the problems arising from their combustion has led to widespread research on renewable energy resources. Currently, biogas has a great potential as renewable energy in Malaysia due to abundantly available resources. According to Malaysia Department of Veterinary Services, poultry industry in Malaysia was growing annually which contributed in the rising amount of poultry manure wastewater (PMW). Biogas resources from wastewater have potential energy of 7800 TJ/y. Thus, utilizing the increasing amount of PMW, into biogas production was suggested in this study. The design of experiment (DOE) of this study utilized Response Surface Method (RSM) by Design Expert Software. Firstly, biological treatment using soil water was conducted because according to few researchers, more than 1000 mg/L of ammoniacal nitrogen (AN) present in PMW will cause inhibition. The initial AN concentration of PMW used in this study was up to 1490 mg/L. The best suggested condition for PMW treatment from the software was agitation (0 rpm), reaction time (5 hours), type of soil water (SSW), soil to water ratio (1:6) and PMW: soil water (1:4). Utilization of this conditions resulted in 81.90% of AN removal. Next, factorial analysis was conducted to analyze factors affecting biogas production. From the result, agitation gave the highest contribution to biogas production by 24.09%. This showed that agitation was the most affecting factor in this study. Agitation ensures efficient transfer of organic material for the active microbial biomass, to release gas bubbles trapped in the medium and to prevent sedimentation of denser particulate matter. The best suggested condition for factorial analysis of PMW by the software was agitation (120 rpm), reaction time (3 days), substrate to inoculum ratio (4:1), process system (batch), and type of substrate (treated PMW). After factorial analysis, process optimization was conducted. The suggested optimum conditions by the software were validated at agitation (120 rpm) and reaction time (3.3 days). Under this condition, 0.00397 L/g COD of biogas yield was obtained with 30% of methane content. This counts for 5.82% error from predicted value. The result from this study showed that utilization of PMW was a suitable method in biogas production. Along with the process, biological treatment was proved to be applicable as treatment method for AN removal to avoid inhibition.